Therapeutic Strategies Against Cancer Stem Cells in Esophageal Carcinomas - Das, Plabon Kumar; Islam, Farhadul; Smith, Robert A.; Lam, Alfred K. (Frontiers in Oncology, 2021)
Cancer stem cells (CSCs) in oesophageal cancer have a key role in tumour -initiation, progression and therapy resistance. Novel therapeutic strategies to target CSCs are being tested, however, more in-depth research is necessary. Eradication of CSCs can result in successful therapeutic approaches against oesophageal cancer. Recent evidence suggests that targeting signalling pathways, miRNA expression profiles and other properties of CSCs are important strategies for cancer therapy. Wnt/β-catenin, Notch, Hedgehog, Hippo and other pathways play important roles in proliferation, differentiation, and self-renewal of stem cells as well as of CSCs. All of these pathways have been implicated in the regulation of oesophageal CSCs and are potential therapeutic targets. Interference with these pathways or their components using small molecules could have therapeutic benefits. Similarly, miRNAs are able to regulate gene expression in oesophageal CSCs, so targeting self-renewal pathways with miRNA which could be utilized to as a potential therapeutic option. Moreover, hypoxia plays critical roles in oesophageal cancer metabolism, stem cell proliferation, maintaining aggressiveness and in regulating the metastatic potential of cancer cells, therefore, targeting hypoxia factors could also provide effective therapeutic modalities against oesophageal CSCs. To conclude, additional study of CSCs in oesophageal carcinoma could open promising therapeutic options in oesophageal carcinomas by targeting hyper-activated signalling pathways, manipulating miRNA expression and hypoxia mechanisms in oesophageal CSCs.